PROSES SELEKSI CALON KARYAWAN PADA PT XXX (Studi kasus di Sidoarjo) - Amallia Dicanuary Abhellina; Roziana Ainul Hidayati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
PT. XXX is a company engaged in outsourcing which is located in the Sidoarjo area. The purpose of this study is to find out the causes of fraud and the efforts that must be made by companies to minimize fraud that often occurs when selecting prospective employees at PT.XXX. The method used in this research is by using descriptive qualitative method. The data sources used in this research are primary data and secondary data. Data collection techniques used in this study were observation and interviews. The researcher made observations through the process of recording and observing during the activity. The interviews conducted by the researchers were direct interviews with 3 informants, namely the HRD Manager, Recruitment Leader and Recruitment Staff. Judging from the phenomena that the researchers found, there was no special supervisory team formed by PT. XXX during the selection process for prospective employees, causing a lot of fraud that occurred during the selection process.